Exploring Grammatical Errors in English Writing Made by EFL Saudi Learners at Al-Dayer University College, Jazan University - Abdulrahman Ali Al Towity (Taez University, 2022)
Error analysis is a way to investigate errors in the second or foreign language acquisition. This study of error analysis is part of an investigation of the process of English language learning. Making grammatical errors by students of English as a Second/Foreign Language (ESL/EFL) in their writing is unavoidable and this makes the task of language teachers rather difficult to help learners overcome this stage. Some learners feel frustrated dealing with the same mistakes repeatedly. Therefore, language teachers should investigate students' common mistakes and seek for the reasons of making them. Thus, the researcher, as a teacher, in this study aims at describing the grammatical errors committed by Arabic-speaking learners of EFL. This research is based on the analysis of writing compositions done by the students at Al-Dayer university college, Jazan University. The research is conducted based on the comprehensive error taxonomy of Byrd & Benson (1994). The errors were classified into three parts, 'The Most Serious Errors', 'Intermediate Errors', and 'Punctuation and Mechanic Problems'. It is found that learners made various grammatical errors and the most common errors occurred in the third group, 'Punctuation and Mechanic Problems' (32.7% of the students). The second highest number of errors lay in the first category, 'The Most Serious Problems' (26.9% of the students). The second category in the table, 'Intermediate Problems', came as the least number of errors; 18.3% of the students made grammatical mistakes in it. It seems that L1 (Arabic) influence is the cause of so many errors that are committed by students such as 'spelling', 'verb tense', 'word form', 'run-on sentences' and 'comma splice'. The study suggested some recommendations for further studies and also suggested to take in consideration students mistakes in the materials of grammar and writing courses so as students' writing in English could be improved and grammatical errors be reduced